(untitled) (SciELO Preprints, 2026)
Objective: To develop and validate standardized glycemic biomarkers capable of capturing intermediate-term glycemic control (approximately eight weeks), thereby addressing the temporal gap between fructosamine and glycated hemoglobin (HbA1c). Methods: A methodological validation study was conducted using laboratory results from individuals with type 1 and type 2 diabetes mellitus (DM). HbA1c and fructosamine values were normalized through min–max transformation anchored to established clinical reference intervals. Serial measurements of HbA1c, fructosamine, and fasting plasma glucose were obtained over an eight-week period to examine temporal associations among the biomarkers. Pearson and Spearman correlation analyses, receiver operating characteristic (ROC) curve analysis, one-way analysis of variance, and Bland–Altman methods were employed to assess accuracy, agreement, and discriminative performance of the standardized indices. Results: Normalized HbA1c and fructosamine exhibited strong correlations with each other and with glycemic control derived from multiple glucose measurements throughout the eight-week interval. For both biomarkers, the upper limit of normality consistently approximated a normalized value of 1.0. A composite index integrating normalized HbA1c and fructosamine significantly enhanced discrimination between controlled and uncontrolled DM, yielding an area under the ROC curve superior to that of either biomarker alone. Conclusions: Standardized glycemic biomarkers represent a feasible and clinically meaningful strategy for assessing intermediate-term glycemic control, with potential applicability in routine DM management and in supporting earlier and more informed therapeutic decision-making.